2023
DOI: 10.3390/jcm12113712
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Functional Outcomes at 3 Months in Critical COVID-19 Survivors Hospitalized during the First, Second, and Third Pandemic Waves

Abstract: Introduction: Despite improved management of patients with COVID-19, we still ignore whether pharmacologic treatments and improved respiratory support have modified outcomes for intensive care unit (ICU) surviving patients of the three first consecutive waves (w) of the pandemic. The aim of this study was to evaluate whether developments in the management of ICU COVID-19 patients have positively impacted respiratory functional outcomes, quality of life (QoL), and chest CT scan patterns in ICU COVID-19 survivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A previous study suggests that the use of glucocorticoids or immunomodulatory therapy may contribute to PFT improvement over time 38 . This did not concern the patients in our study since these treatment options were not available during the initial wave of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggests that the use of glucocorticoids or immunomodulatory therapy may contribute to PFT improvement over time 38 . This did not concern the patients in our study since these treatment options were not available during the initial wave of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Since long COVID can lead to increased f atigue and decreased exercise capacity 4 , the six-minute walk test (6MWT) is an of ten-used outcome parameter in clinical trials including patients with long COVID.…”
Section: To the Editormentioning
confidence: 99%
“…Since long COVID can lead to increased fatigue and decreased exercise capacity [ 4 ], the 6-min walk test (6MWT) is an often-used outcome parameter in clinical trials including patients with long COVID. The 6MWT is a valid tool, with a good test–retest reliability to test patients' functional exercise capacity, to evaluate the response of a therapeutic intervention or to assess prognosis [ 5 ].…”
mentioning
confidence: 99%
“…We have recently shown that, when comparing outcomes of patients handled during these first waves, the use of glucocorticoids, as well as tocilizumab, was associated with improvements in the number of affected segments in chest CT, FEV1, TLC, and DLCO at 3 months. 37 However, due to the small size of the sample, changes over time can be hampered by sparse-data bias. An additional source of limitation is the use of threshold in predicted values and not the Global Lung Initiative (GLI) reference value to interpret PFT.…”
Section: Limitationsmentioning
confidence: 99%